Pedagogy of Peacefulness as an Effort of Peaceful Education at School - Eva Imania Eliasa; Sunaryo Kartadinata; Ilfiandra Ilfiandra; Juntika Nurihsan (Universitas Mathla'ul Anwar Banten, 2019)
Based on the phenomenon occurred at all level of education, it was found that the circumstances of the schools were unsafe and uncomfortable for students and academics. There were a number of direct and indirect violence carried out at schools and it had impacts on physical and psychological health of students. There was no existence of positive peace in the form of structural violence, socio-cultural violence, ecological violence and negative peace such as tribal warfare, fights and aggression. What happened actually although the nature of man in conscience had the basic harmony and desire to live together in tranquility? Therefore, the common perception of the concept of peace and peace pedagogy was needed to be created. Teachers as peace educators, thus, played an important role as a figure that had the personality of peace in the classroom and at school. The teacher as a peaceful personality consisted of three components: peaceful states, attitudes, and behavior that were consistent across one’s life spaces and life span. Moreover, the school also needed to develop an educational approach in the curriculum in synergy with the goals of education.